THE ROLE OF THE UNITED STATES IN SHAPING CONTEMPORARY GLOBAL SECURITY ARCHITECTURE - Sadibakosev Khabibullo Shodiboy o‘g‘li (Modern American Journals, 2025)
The United States has played a pivotal role in shaping the current structure of international security, particularly since the beginning of the 21st century, leveraging its significant military and economic power. This article explores the key opportunities and challenges facing the U.S. as it seeks to safeguard its national interests, promote regional stability, and respond to emerging security threats. It analyzes how the U.S. asserts its global influence, engages in power projection, and cooperates multilaterally, while also addressing the necessity of adjusting to shifting geopolitical realities. Furthermore, the article examines ongoing debates surrounding American leadership, including critiques of unilateral actions, intervention in the domestic affairs of other states, and the complexities of aligning security objectives with broader global issues. Ultimately, this study offers a comprehensive perspective on how U.S. policies affect global order, influence regional dynamics, and shape the future of international security systems.